Present state of understanting of the breakdown of passivitty and repassivation - Galvele, José Rodolfo (Comisión Nacional de Energía Atómica; Argentina, 1977)
Fil: Galvele, José Rodolfo Comisión Nacional de Energía Atómica; Argentina